Accelerator for Ultrafast Laser Serial Production: Interaction of important components opens up new possibilities. Issue 4 (1st August 2019) - Ryll, Joachim; Holtkamp, Jens; Eifel, Stephan
Abstract: The world of serial applications has long been denied the possibility of ablation processes with ultrafast pulsed laser radiation due to high investment costs and low ablation rates. Nowadays, process scaling with advanced beam shaping technologies make use of the available high laser powers and therefor opens up possibilities for serial processing of individual components. But the exclusive focus on the main time of laser processing is not enough for a production system. Only the combined operation of handling systems, measurement technology, and process automation allow the ultrafast laser technology to spread further into volume markets.